HUBUNGAN SELF EFFICACY DAN DUKUNGAN PASANGAN DENGAN SELF CARE BEHAVIOUR PENDERITA DM TIPE II DI KLINIK KITAMURA - Wahyuni, Sri (School of Nursing, Faculty of Medicine, Tanjungpura University, 2021)
Background: Diabetes mellitus (DM) is a chronic disease that requires continuous self-care. Diabetes that is often not controlled can lead to complications and death. In increasing self-care behavior, there are several factors that influence, one of which is self-efficacy and spousal support.Method: This cross-sectional study involved 51 respondents, selected through a purposive sampling method. Instruments used include a set of questionnaires of Diabetes Management Self Efficacy (DMSE), Spousal Support, and Summary of Diabetes Self Care Activities (SDSCA). Spearman